BASIC CONCEPTS OF PUBLIC DIPLOMACY (INNOVATIVE ECONOMY, 2023)
Khomenska I.V., Ivashchuk O.V. BASIC CONCEPTS OF PUBLIC DIPLOMACYPurpose. The aim of the article is to identify the basic concepts of the formation of public diplomacy.Methodology of research. The theoretical and methodological basis of the research is the fundamental provisions of the modern theory of international economic relations, scientific works of scientists. In the process of research, general scientific and special methods were used, in particular: dialectical, monographic and systemic analysis – to substantiate the essence of the functioning of modern diplomacy; analysis and synthesis – for studying the object and subject of research; abstract and logical – during the formation of theoretical generalizations, assumptions, conclusions.Findings. Distinctive features of modern diplomacy, new forms and methods of conduct are considered. The historical development of public diplomacy is defined. It is emphasized that in the information age, public diplomacy acquires a new character and covers wider areas. It is substantiated that the European integration vector of Ukraine's foreign policy forces more active use of public diplomacy tools. The peculiarities of the formation of the image and reputation of the country, including with the help of tools of public diplomacy, are revealed. The strategic aspect of the development of Ukraine's public diplomacy through countering the threats that are growing in war conditions is argued.Originality. The theoretical concepts of public diplomacy and the peculiarities of the implementation of its tools are revealed. The theoretical and methodological approaches to uncovering the essence of public diplomacy on the basis of the generalization of existing scientific approaches, the involvement of soft power in the implementation of public diplomacy projects have gained further development. The strategic vectors of Ukraine's public diplomacy through countering modern threats are substantiated.Practical value. The obtained results of the research can be used for further scientific developments on improving the theoretical basis of public diplomacy and increasing its role in international relations.Key words: global transformations, cultural diplomacy, international security, international image, propaganda, public diplomacy, social and economic processes, Public Diplomacy Strategy of the Ministry of Foreign Affairs of Ukraine.
Keywords: global transformations; cultural diplomacy; international security; international image; propaganda; public diplomacy; social and economic processes; Public Diplomacy Strategy of the Ministry of Foreign Affairs of Ukraine.